Immunoglobulin Gamma-Like Therapeutic Bispecific Antibody Formats for Tumor Therapy - Shixue Chen; Lingling Li; Fan Zhang; Yu Wang; Yi Hu; Lei Zhao (Journal of Immunology Research)
Bispecific antibodies (BsAbs) are a sort of dual functional proteins with specific binding to two distinct targets, which have become a focus of interest in antibody engineering and drug development research and have a promising future for wide applications in cancer immunotherapy and autoimmune disease. The key of clinical application and commercial-scale manufacturing of BsAbs is the amenability to assembly and purification of desired heterodimers. Advances in genetic engineering technology had resulted in the development of diverse BsAbs. Multiple recombinant strategies have been used to solve the mispairing problem between light and heavy chains, as well as to enforce accurate dimerization of heterologous heavy chains. There are 23 platforms available to generate 62 BsAbs which can be further divided into IgG-like ones and fragment-based ones, and more than 50 molecules are undergoing clinical trials currently. BsAbs with IgG-like architecture exhibit superior advantages in structure (similar to natural antibodies), pharmacokinetics, half-life, FcR-mediated function, and biological activity. This review considers various IgG-like BsAb generation approaches, summarizes the clinical applications of promising new BsAbs, and describes the mechanism of BsAbs in tumor therapy.